2017
DOI: 10.3389/fnhum.2017.00573
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Conventionality in Co-speech Gestures Involves the Fronto-Temporal Language Network

Abstract: Face-to-face communication is multimodal; it encompasses spoken words, facial expressions, gaze, and co-speech gestures. In contrast to linguistic symbols (e.g., spoken words or signs in sign language) relying on mostly explicit conventions, gestures vary in their degree of conventionality. Bodily signs may have a general accepted or conventionalized meaning (e.g., a head shake) or less so (e.g., self-grooming). We hypothesized that subjective perception of conventionality in co-speech gestures relies on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 110 publications
(167 reference statements)
0
9
0
Order By: Relevance
“…In terms of phoneme processing, the left middle temporal cortex would be expected to play a major role, as it is an integral part of speech and word processing (Hickok and Poeppel, 2007). In fMRI studies, the peak location for differences between our groups found for the beta band has been frequently associated with activations during listening to speech in various ways (Narain et al, 2003;Oechslin et al, 2010;Straube et al, 2013b;Nagels et al, 2013;Evans et al, 2016, Wolf et al, 2017.…”
Section: Isc Differences Between Dyslexics and Controlsmentioning
confidence: 86%
“…In terms of phoneme processing, the left middle temporal cortex would be expected to play a major role, as it is an integral part of speech and word processing (Hickok and Poeppel, 2007). In fMRI studies, the peak location for differences between our groups found for the beta band has been frequently associated with activations during listening to speech in various ways (Narain et al, 2003;Oechslin et al, 2010;Straube et al, 2013b;Nagels et al, 2013;Evans et al, 2016, Wolf et al, 2017.…”
Section: Isc Differences Between Dyslexics and Controlsmentioning
confidence: 86%
“…Rather all kinds of context, including multimodal cues, are processed simultaneously and immediately (Hagoort and van Berkum, 2007 ). Numerous studies have provided evidence for similar processing of gesture and speech in terms of semantic and temporal integration (Özyürek et al, 2007 ; Hubbard et al, 2009 ; Straube et al, 2009 ; Habets et al, 2011 ; Dick et al, 2014 ; Yang et al, 2015 ; Peeters et al, 2017 ), as well as in terms of perceiving conventionalized meaning (Andric et al, 2013 ; Wolf et al, 2017 ). In addition, there is evidence that prosodic information from visual and vocal channels is treated similarly by the brain, with gestural beats functioning as visual prosody complementary to speech prosody (Biau et al, 2016 ).…”
mentioning
confidence: 99%
“…To date, studies on gesture-speech integration have employed diverse methodologies, whether in terms of the definition for iconic gestures used, the task or even instructions given to participants. And as suggested by Wolf et al (2017) , the interpretation of verbal and gestural information can be modulated according to the task and/or instruction given to the participants. Our aim is, therefore, to put into perspective the data found in the field of iconic gesture-speech integration by specifically highlighting the methodological variations.…”
Section: Introductionmentioning
confidence: 99%
“…Our aim is, therefore, to put into perspective the data found in the field of iconic gesture-speech integration by specifically highlighting the methodological variations. Indeed, the diversity of results yielded in this field could be explained by (1) non-identical testing methods ( Wolf et al, 2017 ) (2) overlooking the specificities of iconic gestures or (3) a non-integrative interpretation of results.…”
Section: Introductionmentioning
confidence: 99%